Essays on operational risk in the banking industry - Persand-Gujadhur Gya, Hurvashee (2020)
This thesis consists of three distinct essays on operational risk in the U.S. banking industry. The first essay investigates whether operational risk events trigger rating agencies, such as S&P, to downgrade credit ratings of affected U.S. banks over the period 1990 to 2014. Our results suggest that disclosed maximum operational loss as a proportion of market value as well as consequent drops in stock market prices have a negative and significant effect on banks’ credit ratings through its ratings score, provided by S&P. The findings are robust to severe operational risk events with loss amounts exceeding $10 million. We also find that post-Global Financial Crisis, S&P becomes more accurate in issuing credit ratings following the disclosure of the severity of operational risk events.